Effect of Phosphorus-Nitrogen based Flame-Retardant Combined with Zinc Borate on Thermal Stability and Flame Retardancy of Epoxy Clay Nanocomposites - Dhillon, Kismat; Soni, Vishal; Dahiya, J.B. (Asian Journal of Chemistry, 2024)
A phosphorus-nitrogen containing 6,6'-(piperazine-1,4-diyl)bis(6H-dibenzo[c,e][1,2]oxaphosphinine 6-oxide) (DOPO-PZ) flame-retardant was synthesized and its effect combined with zinc borate (ZnB) and nanoclay (NC) on thermal stability and flame retardancy of epoxy resin was studied. Various epoxy composites containing DOPO, DOPO-PZ, ZnB and NC using curing agent diaminodiphenylsulfone (DDS) were prepared. The X-ray diffraction (XRD) and transmission electron microscope (TEM) micrographs of the composites showed intercalated nanostructure of epoxy-clay nanocomposites. In thermogravimetric analysis (TGA), pure epoxy gave 3.4% char yield at 700 ºC in nitrogen atmosphere, while in case of EP/DOPO-PZ/ZnB/NC sample having 1% phosphorus content, 5 wt.% zinc borate (ZnB) and 3 wt.% nanoclay (NC), the char yield is increased to 24.0%. Differential scanning calorimetry (DSC) study showed decrease in the glass transition temperature (Tg) on the addition of flame-retardant due to plasticization effect and increase in Tg on addition of nanoclay due to formation of nanostructure of epoxy composites. The EP/DOPO-PZ/ZnB/NC nanocomposite sample exhibited a limiting oxygen index (LOI) value of 29.2% and passed the UL-94 test with a V-0 rating and thus achieved a sufficient flame retardancy.